Immune therapy of metastatic melanoma developing after allogeneic bone marrow transplant. Issue 1 (December 2015) - Cecchini, Michael; Sznol, Mario; Seropian, Stuart
Abstract Metastatic melanoma is frequently treated with immune activating therapy, which poses a theoretical risk of inducing graft versus host disease (GVHD) in those who have received allogeneic stem cell transplantation. The literature reporting the safety of immunotherapy in post transplant patients is limited. We report two patients with metastatic melanoma who received treatment with immunotherapy after allogeneic stem cell transplantation that did not result in GVHD.